MELAYU DALAM SASTRA INDONESIA: STUDI SATARDJI CALZOUM BACHRI - Zaidan, Abdul Rozak (Jurnal Pujangga, 2010)
The Malayan in the context of Indonesian literature is equal to Java, Sundanese, Bugis, Bali, Madura, and so on. They are parts of multicultural Indonesian. The meaning of Malayan is every single thing tightens with its language, especially the culture of Malayan. In accordance with this matter, the elements of Malayan in poems by Sutardji have such an aesthetic enchantment in poetry with some couplets, and also found in several poems O, Amuk, Kapak. Moreover, it is something that he fully realized. It is proven through the theory of Sutardji Calzoum Bachri concerning about the mysterious connection between couplets and the contents of poetry.